2014
DOI: 10.1142/s2010132514500278
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Upper-Heating System in Solar Water Storage Tank

Abstract: Thermal strati¯cation in the water storage tank of solar heating system is essential to increase the collection e±ciency. We previously investigated the strati¯cation performance of side-heating system, where the hot water returning from the collector heats up the side wall of storage tank. Subsequently, we studied an evolved heating system for further improvement, where we added an upper-heating to the side-heating. Here we thoroughly examine the strati¯cation performance of the evolved heating system using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The most basic method is a heat exchange coil arranged only in the lower part of the heat storage tank and a constant flow rate. Contrary to this lower installation of heat exchange coil, our previous studies showed that the upper and side heating of the storage tank is more effective for higher stratification performance [26], as upper heating increases the temperature difference between the top and bottom of the storage tank. In such system, when the solar radiation condition is not strong, it can be seen that operating only the bottom coil or reducing the flow rate improves the solar energy collection efficiency by about 7%.…”
Section: Simulation Methods and System Modelingmentioning
confidence: 81%
“…The most basic method is a heat exchange coil arranged only in the lower part of the heat storage tank and a constant flow rate. Contrary to this lower installation of heat exchange coil, our previous studies showed that the upper and side heating of the storage tank is more effective for higher stratification performance [26], as upper heating increases the temperature difference between the top and bottom of the storage tank. In such system, when the solar radiation condition is not strong, it can be seen that operating only the bottom coil or reducing the flow rate improves the solar energy collection efficiency by about 7%.…”
Section: Simulation Methods and System Modelingmentioning
confidence: 81%
“…Dependence of solar harnessing mainly on a kernel solar collector that transfers the solar radiation into heat energy is well known (Son et al, 2014). Among the available solar collectors, a flat plate collector and the evacuated tube are being used for several applications due to ease in installation in buildings along with relatively low operating and maintenance costs.…”
mentioning
confidence: 99%